Penerapan Pola Pengabdian Kepada Masyarakat Pada Kelompok Tani di Kabupaten Magelang dan Temanggung - Rosa Zulfikhar; Akimi; Budi Purwo Widiarso; Muzizat Akbarrizki (PT FORMOSA CENDEKIA GLOBAL, 2022)
The agricultural sector has an important role in supporting the national economy. The role is the creation of food security, a contributor to gross domestic product, job creation, poverty alleviation, a provider of food and industrial raw materials, a source of community income. All of the respondents in this study have farmed livestock. The application of the pattern of community service to farmer groups in Magelang Regency and Temanggung Regency shows that most farmers/breeders are of productive age and can increase agricultural productivity after receiving guidance from the Ministry of Agriculture program. Communication patterns have the same perception of group goals, division of tasks with members' abilities, trust in the group, level of satisfaction with the group, channels for communicating id / ideas for group progress and the achievement of member goals through the group. Trust in the group and the level of satisfaction with the group increased because of the guidance from the Ministry of Agriculture.